Pregabalin beneficial effects on sleep quality or health-related quality of life are poorly correlated with reduction on pain intensity after an 8-week treatment course - Perez Lloret, Santiago (2012)
BACKGROUND: Pregabalin (PGB) has been shown to improve sleep quality and health-related quality of life (HRQoL) as well as pain intensity in patients with neuropathic pain. OBJECTIVE: The objective of the study was to explore the magnitude of the correlations between changes in pain intensity, sleep quality, and HRQoL after PGB treatment. METHODS: One hundred thirty-eight patients with neuropathic pain of any origin and without an adequate response to analgesics received an 8-week treatment course of PGB in an open-label fashion. Pain intensity, sleep quality, and HRQoL outcomes were evaluated at baseline and at week 8 by means of an 11-point (0-10) numerical rating scale (NRS), the Pittsburgh Sleep Quality Index (PSQI), and the EuroQol health-state visuoanalogic scale (EQ-5D VAS) score, respectively. RESULTS: At week 8, mean PGB dose was 166.7 ± 7.8 mg/d. Pain intensity NRS score, PSQI total score, and EQ-5D VAS score were improved by 66.5% ± 1.9%, 40.0% ± 3.6%, and 26.4% ± 4.7% (all P < 0.01), respectively. Correlations between percent change from baseline in pain NRS score and PSQI total score or EQ-5D VAS scores were r = 0.36 (P < 0.01, R = 0.11) and r = -0.20 (P < 0.02, R = 0.05), respectively. A multivariate logistic regression analysis disclosed that PSQI score change below the median (ie, a better outcome) was related to higher EQ-5D VAS score change (odds ratio, 2.15; 95% confidence interval, 1.09-4.25), whereas pain intensity NRS score change below the median was not (odds ratio, 1.58; 95% confidence interval,0.78-3.23). CONCLUSIONS: In our study, PGB-related improvements in sleep quality and HRQoL were marginally related to reductions in pain intensity in patients with neuropathic pain. Improvement in sleep quality was a significant predictor of better HRQoL, whereas pain intensity reduction was not.